Transatlantic MRAs: lessons for TTIP? - Pelkmans, Jacques (Brussels, 2015)
"It is striking that there is little or no mention in the TTIP debate so far of the US-EU Mutual Recognition Agreement (MRA) concluded in 1998. At the time, expectations of the gains from the MRA were high. One should expect the MRA to be instructive for TTIP and entail some lessons to be learned for today’s attempt to lower technical barriers to trade (TBTs) across the North Atlantic. We offer an analysis of the 1998 MRA, the difficulties in the prior negotiations and those during the implementation phase, the subsequent and present status of sectoral approaches. The MRA experience revealed clearly how difficult it is to accomplish the acceptance of all relevant aspects of conformity assessment of the trading partner for the mere purpose of testing and certifying export goods on the requirements of the importing economy. The MRA has succeeded only in a few sectors. However, the ambition in TTIP with respect to TBTs is said to go so much further. It is therefore important for all those involved or interested in TTIP to learn the lessons of this early exercise in lowering TBT costs.